Tipuri de bacterii implicate în mamite la bovine - Caius Stoichescu; Romeo Teodor Cristina (Medicamentul Veterinar)
The microbial etiology of mastitis includes a variety of bacterial species, yeasts, and even some viruses. In this regard, over 38 types of microorganisms have been identified, capable of producing inflammation of the mammary gland. In this bibliographic report, the main mastitis in cows are presented, (staphylococcal, streptococcal, pyobacillary (Summer Mastitis), colibacillary, mycoplasmal, yersinic, pseudomonic, brucella, pasteurellic, mycoplasmal, actinobacillary, leptospirosis, necrobacillary, tuberculous, nocardial, produced by Dermatophilus, chlamydial, clostridial, produced by the genera Haemophilus Serattia, Listeria, Prototheca). Their geographical distribution, economic importance, etiology, epidemiological characteristics, clinical picture is presented.